PEMANFAATAN BUAH TERONG BELANDA DAN BUAH BELIMBING WULUH DALAM PEMBUATAN SIRUP - Patrisia Marlina Br Sinaga; Faizah Hamzah; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Syrup is a type of beverage in the form of a thick solution with a variety of flavors that contain high sugar, which is between 50-65%. The purpose of this study was to obtain the right one for making syrup corresponding SNI 01-2544-2013.This research was used Completely Randomized Design (CRD) with 5 treatments was used replications in order to the obtain 15 experiment unit. The treatment was a mixture ratio of fruit tamarillo and ratio wuluh starsfruit such as TB1=(90:10), TB2=(80:20), TB3=(70:30), TB4 = (60:40), and TB5 = (50:50). Data were statistically anallyzed by Analysis of Variance (ANOVA) and continued witht DMRT (Duncant’s New Multiple Range Test) at level of 5%. The results showed that formulation affect on the value of pH, sucrose concentration, viscosity, colour, flavour, taste and taste overall assessment basis hedonic.The best research results of syrup in treatment TB1 (90:10%) the result of syrup has a pH value 4,70, sucrose concentration 64,86%, viscosity 257,02 cP. The result of the descriptive test of the syrup from the best treatment was a colour of score red 4,73, aroma with score 4,66 flavorful and was a taste of score 3,36 sweet acidity, and overall assessment hedonic liked by panelist with a score of 4,54.